Study of dietary pattern in women who develop hypertensive disorders of pregnancy - Bachani, Sumitra; Gaikwad, Harsha S.; Nischal, Sakshi; Kashika,; Tanwar, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The upcoming evidence regarding role of diet in various disorders is compelling. This study was conducted to study the role of diet in hypertensive disorders of pregnancy apart from the already established role of genetics and biomarkers. Objectives were to study the dietary pattern in antenatal women, to study the association of dietary factors in development of hypertensive disorder of pregnancy in antenatal women. Methods: This was a prospective study conducted in a tertiary care hospital from January 2021 to November 2021 in North India. A total of 50 pregnant women were included in their first trimester. Detailed dietary history was taken as per 24 hour recall method by a qualified dietician. The amount and proportion of various food nutrients i.e. carbohydrate, fats, proteins, fruits and vegetables, milk and milk products were calculated. These women were followed till delivery and studied for the development of hypertensive disorders of pregnancy. Results: It was observed that there was lesser mean intake of fruits (235.71 vs 241.11 gm) and vegetables (257.14 vs 277.78 gm) in women who developed hypertensive disorder than among those who did not. However, the intake of fat was similar in both groups. Conclusions: Our study shows that intake of more fruits and vegetables has a protective role in development of hypertensive disorders of pregnancy.